Preparation method of three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material
By introducing crystalline aluminum dihydrogen phosphate into the phenolic resin and combining it with three-dimensional continuous carbon fibers, a fiber-reinforced resin-based composite material with a thermal insulation temperature of up to 1200°C and a linear ablation rate of less than 0.01 mm/s was prepared, which solved the problem of insufficient thermal insulation and mechanical properties of the material in the prior art.
Patent Information
- Application Number
- CN202411713748.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The prior art cannot prepare fiber-reinforced resin-based composite materials with thermal insulation temperatures up to 1200°C or above and linear ablation rate is less than 0.01 mm/s, and the requirements for wall flow pressure and bending strength cannot be met when flying at high speed.
Using the preparation method of a three-dimensional continuous carbon fiber reinforced organic inorganic hybrid resin-based composite material, the composite material is prepared by introducing crystalline aluminum dihydrogen phosphate as an inorganic precursor into the phenolic resin to form an aluminum phosphate-phenolic hybrid resin, which is adhered through the carbon fiber framework structure, and the composite material is prepared by vacuum impregnation and gradient cross-linking curing processes.
The insulation temperature is achieved above 1200℃, the linear ablation rate is less than 0.01mm/s, and the bending strength reaches 7.12MPa under 5kN load, and the compression strength can reach 12MPa, meeting the requirements of high-temperature thermal insulation and mechanical properties of materials by high-speed aircraft.
Smart Images

Figure CN119552401A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a fiber-reinforced resin-based high-temperature heat-insulating composite material. Background Art
[0002] The rapid development of aerospace reentry vehicles has placed higher and higher requirements on thermal protection materials. Among the current thermal protection materials, polymer-based composite materials have more obvious advantages over ceramic-based thermal protection materials, metal-based thermal protection materials, etc. in certain special use conditions. As the most widely used polymer-based composite materials, phenolic resin-based composite materials are widely used in the surface materials of the reentry vehicle return capsule. When the vehicle returns to the atmosphere, it is affected by the surface heat flow and the wall friction aerodynamic heat. Its surface temperature can often reach more than 1000°C, which has long reached the thermal decomposition temperature of the phenolic resin polymer matrix. In order to prevent the phenolic resin from being decomposed by heat prematurely, resulting in the shrinkage of the material volume and the destruction of the microstructure, the ablation rate increases while the residual weight rate decreases, resulting in the heat being unable to be effectively dissipated on the surface. The method of introducing inorganic aluminum phosphate as a precursor is used to effectively protect the phenolic resin in the polymer matrix, absorb more heat during the heating process, thereby reducing the temperature of the back wall of the reentry vehicle, protecting the internal components and extending the service life of the vehicle. In addition, when the spacecraft's return capsule returns to Earth, the surface must also take into account the flow pressure from the wall, which also places higher requirements on the compression and bending strength of the material.
[0003] Traditional fiber-reinforced thermal insulation resin-based composite materials are mainly composed of phenolic resin / rubber, continuous fiber cloth, and ceramic particle composite systems. The insulation temperature is between 400℃ and 600℃ at the same thickness, and the linear ablation rate is often between 0.03mm / s and 0.05mm / s. With the continuous increase in the speed of reentry vehicles, the service conditions on the surface of the return capsule are becoming more and more severe. Resin-based composite materials are gradually used as thermal insulation materials on the surface of the return capsule. However, there are no reports of resin-based composite material systems with insulation temperatures above 1200℃ and a linear ablation rate of less than 0.01mm / s. In addition, in response to the flow pressure from the wall during high-speed flight, resin-based composite materials must also have good compressive strength and flexural strength. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the prior art cannot prepare fiber-reinforced resin-based composite materials with an insulation temperature of more than 1200°C and a linear ablation rate lower than 0.01mm / s, and to provide a method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material.
[0005] A method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material, wherein the composite material is aluminum phosphate-phenolic hybrid resin / carbon fiber cloth, wherein the carbon fiber cloth is the skeleton structure of the composite material, and the aluminum phosphate-phenolic hybrid resin is distributed in the carbon fiber skeleton structure in a penetrating attachment manner; the preparation method is specifically completed according to the following steps:
[0006] 1. Pretreatment of three-dimensional continuous carbon fiber:
[0007] Removing excess sizing agent and impurities on the surface of the three-dimensional carbon fiber to obtain pretreated carbon fiber;
[0008] 2. Preparation of hybrid resin prepreg:
[0009] ①, dissolving phenolic resin in an organic solvent, and stirring thoroughly to obtain a phenolic resin solution;
[0010] The mass fraction of the phenolic resin solution described in step 2① is 30% to 60%;
[0011] ②, dissolving the crystalline aluminum dihydrogen phosphate powder modified by the curing agent in an organic solvent, and stirring well to obtain an aluminum dihydrogen phosphate inorganic solution;
[0012] The mass fraction of the inorganic aluminum dihydrogen phosphate solution described in step 2② is 30% to 60%;
[0013] ③. Mix the phenolic resin solution and the aluminum dihydrogen phosphate inorganic solution, stir until there is no excess flocculent precipitate in the solution, and let it stand to obtain a hybrid resin prepreg;
[0014] 3. Preparation of fiber-reinforced hybrid resin:
[0015] ①, pour the hybrid resin prepreg into a vacuum impregnation container, then press the pretreated carbon fiber into the hybrid resin prepreg, control the internal pressure and temperature of the vacuum drying oven, and then impregnate for a period of time, and then take the wet fiber out of the vacuum impregnation container to obtain a wet fiber precursor;
[0016] ②, placing the wet fiber precursor in the air and letting it stand for a period of time, and then transferring it to an electric heating blast drying oven for sufficient drying to obtain a fiber-reinforced resin-based composite material prepolymer to be cured;
[0017] ③. Place the fiber-reinforced resin-based composite material prepolymer to be cured in an electric blast drying oven at room temperature, raise the temperature in the electric blast drying oven from room temperature to the curing temperature, perform gradient cross-linking curing in the range from room temperature to the curing temperature, and exhaust the gas in time. After the curing is completed, take out the obtained composite material and replace the solvent with anhydrous ethanol. Replace the replacement solution at intervals until the solution has no obvious color change, and then dry to obtain a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material.
[0018] Principles and advantages of the present invention:
[0019] 1. The purpose of introducing crystalline aluminum dihydrogen phosphate as an inorganic precursor in the phenolic resin solution of the present invention is that crystalline aluminum dihydrogen phosphate will undergo thermal decomposition and phase change under high temperature ablation conditions, which is an endothermic process and consumes a large amount of ablation heat. In addition, AlPO4, Al2O3, SiO2, etc. generated during the ablation process are excellent temperature-resistant and heat-insulating fillers, which greatly slow down the transfer of ablation heat inside the composite material. When the surface temperature is above 1500°C, the back surface temperature is only about 300°C, which is much lower than that in the published patent (CN10935 4823) at 400-500°C, and under the action of oxyacetylene and propane ablation, the linear ablation rate of the material is only about 0.0092 mm / s, which is lower than 0.015 mm / s in the published patent (CN109354823) and 0.018-0.035 mm / s in the published patent (CN111761895); the flexural strength of the three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material prepared by the present invention reaches 7.12 MPa under a load of 5 kN, and the compressive strength can reach 12 MPa;
[0020] 2. The present invention has prepared a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material with a thermal insulation of more than 1200°C, which is of great significance to the development of thermal protection of ablative materials on the surface of my country's re-entry vehicles.
[0021] The invention can obtain a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material with a heat insulation of more than 1200°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a flowchart of the method of the present invention;
[0023] Figure 2 The three-dimensional carbon fibers after the sizing agent is removed in Example 1 are photographs, wherein (a) is a macroscopic optical photograph and (b) is a SEM photograph;
[0024] Figure 3 This is a comparison chart of the back wall temperature when the surface temperature is stabilized at 1500°C under propane ablation conditions;
[0025] Figure 4 The photograph and SEM image of a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material prepared in Example 2 after ablation assessment;
[0026] Figure 5 Linear ablation rate diagrams of a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material prepared in Example 1, Comparative Example 1, Example 2, Comparative Example 2, Example 3, and Comparative Example 3, respectively;
[0027] Figure 6 The flexural strength diagrams of a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material prepared in Example 1, Example 2, and Example 3, respectively. DETAILED DESCRIPTION
[0028] Specific implementation method 1: This implementation method is a method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material, wherein the composite material is aluminum phosphate-phenolic hybrid resin / carbon fiber cloth, wherein the carbon fiber cloth is the skeleton structure of the composite material, and the aluminum phosphate-phenolic hybrid resin is distributed in the carbon fiber skeleton structure in a penetrating attachment manner; the preparation method is specifically completed according to the following steps:
[0029] 1. Pretreatment of three-dimensional continuous carbon fiber:
[0030] Removing excess sizing agent and impurities on the surface of the three-dimensional carbon fiber to obtain pretreated carbon fiber;
[0031] 2. Preparation of hybrid resin prepreg:
[0032] ①, dissolving phenolic resin in an organic solvent, and stirring thoroughly to obtain a phenolic resin solution;
[0033] The mass fraction of the phenolic resin solution described in step 2① is 30% to 60%;
[0034] ②, dissolving the crystalline aluminum dihydrogen phosphate powder modified by the curing agent in an organic solvent, and stirring well to obtain an aluminum dihydrogen phosphate inorganic solution;
[0035] The mass fraction of the inorganic aluminum dihydrogen phosphate solution described in step 2② is 30% to 60%;
[0036] ③. Mix the phenolic resin solution and the aluminum dihydrogen phosphate inorganic solution, stir until there is no excess flocculent precipitate in the solution, and let it stand to obtain a hybrid resin prepreg;
[0037] 3. Preparation of fiber-reinforced hybrid resin:
[0038] ①, pour the hybrid resin prepreg into a vacuum impregnation container, then press the pretreated carbon fiber into the hybrid resin prepreg, control the internal pressure and temperature of the vacuum drying oven, and then impregnate for a period of time, and then take the wet fiber out of the vacuum impregnation container to obtain a wet fiber precursor;
[0039] ②, placing the wet fiber precursor in the air and letting it stand for a period of time, and then transferring it to an electric heating blast drying oven for sufficient drying to obtain a fiber-reinforced resin-based composite material prepolymer to be cured;
[0040] ③. Place the fiber-reinforced resin-based composite material prepolymer to be cured in an electric blast drying oven at room temperature, raise the temperature in the electric blast drying oven from room temperature to the curing temperature, perform gradient cross-linking curing in the range from room temperature to the curing temperature, and exhaust the gas in time. After the curing is completed, take out the obtained composite material and replace the solvent with anhydrous ethanol. Replace the replacement solution at intervals until the solution has no obvious color change, and then dry to obtain a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material.
[0041] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the three-dimensional carbon fiber described in step 1 has a material with three-dimensional distribution, including a three-dimensional fiber needle-punched structure and a three-dimensional fiber braided structure, and the thickness of the three-dimensional fiber is 20 mm. The other steps are the same as those in specific implementation method 1.
[0042] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the method for removing excess sizing agent and impurities on the surface of three-dimensional carbon fiber in step one is: placing the three-dimensional carbon fiber in a muffle furnace, heating it to 250℃~300℃, keeping it warm for 3~4h, cooling it to room temperature with the furnace after keeping it warm, and obtaining pretreated carbon fiber; the heating rate is 1℃ / min. The other steps are the same as those in specific implementation method one or two.
[0043] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the organic solvent described in step 2① and step 2② is anhydrous ethanol, isopropanol or ethylene glycol, and the hybrid resin prepreg dissolved in the alcohol solvent, during the heating process, can form complex pores and interface structures between the three-dimensional continuous carbon fiber skeletons as the solvent dries and evaporates, accompanied by the curing process of the internal resin, and these structures play a role in hindering the heat flow transfer process. The other steps are the same as those of specific embodiments 1 to 3.
[0044] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the preparation method of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent described in step 2② is:
[0045] (1) Dilute 100 parts of concentrated phosphoric acid with 20 to 80 parts of deionized water and stir for a period of time to obtain a phosphoric acid solution;
[0046] (2) adding 20 to 50 parts of aluminum hydroxide powder to the phosphoric acid solution, and stirring for a period of time at a temperature of 80° C. to 90° C. to obtain an inorganic adhesive solution that is not modified by a curing agent;
[0047] (3) adding 2 to 5 parts of a curing agent and 0 to 5 parts of a filler to an inorganic adhesive solution that has not been modified by a curing agent, stirring for a period of time and then air-cooling for a period of time to obtain a zinc ion-modified aluminum phosphate inorganic adhesive precursor solution;
[0048] (4) Transfer the zinc ion modified aluminum phosphate inorganic adhesive precursor solution to a rotary evaporator, remove the water solvent by vacuum rotary evaporation, and then dry to obtain a crystalline aluminum dihydrogen phosphate powder modified by a curing agent. The other steps are the same as those in Specific Embodiments 1 to 4.
[0049] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that: the mass fraction of concentrated phosphoric acid described in step (1) is 50% to 80%; the stirring time in step (1) is 1h to 2h, and the stirring speed is 200r / min to 400r / min; the stirring time at a temperature of 80°C to 90°C in step (2) is 1h to 2h, and the stirring speed is 200r / min to 400r / min; the stirring time in step (3) is 1h to 2h, and the stirring speed is 200r / min to 400r / min. / min~400r / min; the standing time in step (3) is 10min~15min; the curing agent described in step (3) is zinc oxide powder with a particle size of 500 mesh~800 mesh; the particle size of the filler described in step (3) is 80nm~150nm; the filler described in step (3) is one or a combination of silicon powder, mullite whisker, glass fiber, boron nitride, aluminum oxide, boron carbide and silicon carbide; in step (4), the zinc ion modified aluminum phosphate inorganic adhesive precursor solution is dried for 2h~10h. The other steps are the same as those in specific embodiments one to five.
[0050] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the standing time described in step 2 ③ is 10 min to 15 min; the mass ratio of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent, the phenolic resin and the organic solvent in the hybrid resin prepreg described in step 2 ③ is (0.5 to 1.5): (0.5 to 1): (2 to 3). The other steps are the same as those of specific embodiments 1 to 6.
[0051] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the internal pressure of the vacuum drying oven described in step 3① is less than 0.08MPa, and the temperature is 40℃~60℃; the immersion time described in step 3① is 0.5h~1.5h. The other steps are the same as specific embodiments 1 to 7.
[0052] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 3 ②, the wet fiber precursor is placed in air with a humidity not higher than 40% and allowed to stand for 8h to 10h; in step 3 ②, after standing, the fiber precursor is transferred to an electric heating blast drying oven for full drying, which is as follows: first, drying at 90℃ to 100℃ for 0.5h to 1h, and then drying at 120℃ to 150℃ for 2h to 3h. The other steps are the same as those of specific embodiments 1 to 8.
[0053] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that the process of gradient cross-linking curing described in step 3 ③ is: heating from room temperature to 120 ℃ ~ 150 ℃, curing at 120 ℃ ~ 150 ℃ for 2 hours, then heating to 150 ℃ ~ 180 ℃, curing at 150 ℃ ~ 180 ℃ for 3 hours; the heating rate is 0.5 ℃ / min ~ 1 ℃ / min; after curing in step 3 ③, take out the obtained composite material and immerse it in anhydrous ethanol again, replace the anhydrous ethanol every 12 hours, take it out after changing 3 to 4 times, and then dry it at room temperature for 1 to 2 days. The other steps are the same as specific embodiments 1 to 9.
[0054] The following examples are used to verify the beneficial effects of the present invention:
[0055] Embodiment 1: A method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material, wherein the composite material is aluminum phosphate-phenolic hybrid resin / carbon fiber cloth, wherein the carbon fiber cloth is the skeleton structure of the composite material, and the aluminum phosphate-phenolic hybrid resin is distributed in the carbon fiber skeleton structure in a penetrating attachment manner; the preparation method is specifically completed according to the following steps:
[0056] 1. Pretreatment of three-dimensional continuous carbon fiber:
[0057] Remove the excess sizing agent and impurities on the surface of the three-dimensional carbon fiber to obtain the pretreated carbon fiber (the photo of the three-dimensional carbon fiber after removing the sizing agent is shown in FIG. Figure 2 shown);
[0058] The method for removing excess sizing agent and impurities on the surface of the three-dimensional carbon fiber in step 1 is: placing the three-dimensional carbon fiber in a muffle furnace, heating it to 250°C, keeping it warm for 3 hours, and cooling it to room temperature with the furnace after keeping warm to obtain pretreated carbon fiber; the heating rate is 1°C / min;
[0059] The three-dimensional carbon fiber described in step 1 has a material with three-dimensional distribution, wherein the XY direction is a three-dimensional woven structure, the Y direction is a three-dimensional needle-punched structure, and the thickness of the three-dimensional fiber is 20 mm;
[0060] 2. Preparation of hybrid resin prepreg:
[0061] ①, dissolving phenolic resin in an organic solvent, stirring for 10 min at a stirring speed of 150 r / min to obtain a phenolic resin solution;
[0062] The mass fraction of the phenolic resin solution described in step 2① is 50%;
[0063] ②, dissolving the crystalline aluminum dihydrogen phosphate powder modified by the curing agent in an organic solvent, stirring for 4.5 hours at a stirring speed of 300 r / min, to obtain an aluminum dihydrogen phosphate inorganic solution;
[0064] The mass fraction of the inorganic aluminum dihydrogen phosphate solution described in step 2② is 50%;
[0065] The organic solvent described in step 2① and step 2② is anhydrous ethanol;
[0066] ③, mixing the phenolic resin solution and the aluminum dihydrogen phosphate inorganic solution, stirring for 200 min at a stirring speed of 300 r / min, and then standing for 30 min to obtain a hybrid resin prepreg;
[0067] The mass ratio of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent, the phenolic resin and the organic solvent in the hybrid resin prepreg described in step 2③ is 1:1:2;
[0068] 3. Preparation of fiber-reinforced hybrid resin:
[0069] ①, pour the hybrid resin prepreg into a vacuum impregnation container, then press the pretreated carbon fiber into the hybrid resin prepreg, control the internal pressure and temperature of the vacuum drying oven, and then impregnate for a period of time, and then take the wet fiber out of the vacuum impregnation container to obtain a wet fiber precursor;
[0070] The internal pressure of the vacuum drying oven described in step 3① is less than 0.08MPa and the temperature is 40°C;
[0071] The immersion time in step 3① is 1h;
[0072] ②, placing the wet fiber precursor in the air and letting it stand for a period of time, and then transferring it to an electric heating blast drying oven for sufficient drying to obtain a fiber-reinforced resin-based composite material prepolymer to be cured;
[0073] In step 3②, the wet fiber precursor is placed in air with a humidity not higher than 40% and allowed to stand for 10 hours;
[0074] The process of transferring the mixture to an electric hot air drying oven for full drying after standing in step 3② is as follows: first drying at 95°C for 1 hour, and then drying at 150°C for 2 hours;
[0075] ③. Put the fiber-reinforced resin-based composite material prepolymer to be cured into an electric blast drying oven at room temperature, raise the temperature in the electric blast drying oven from room temperature to the curing temperature, perform gradient cross-linking curing in the range from room temperature to the curing temperature, and exhaust the gas in time. After the curing is completed, take out the obtained composite material and immerse it in anhydrous ethanol again. Replace the anhydrous ethanol every 12 hours, take it out after 4 changes, and then dry it at room temperature for 2 days to obtain a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material;
[0076] The gradient cross-linking curing process described in step 3③ is: heating from room temperature to 120°C, curing at 120°C for 2 hours, then heating to 150°C, and curing at 150°C for 3 hours; the heating rate is 1°C / min.
[0077] The preparation method of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent described in step 2② described in Example 1 is:
[0078] ① Dilute 100 parts of concentrated phosphoric acid with 45 parts of deionized water and stir for a period of time to obtain a phosphoric acid solution;
[0079] ②, add 25 parts of aluminum hydroxide powder to the phosphoric acid solution, and then stir for a period of time at a temperature of 80°C to obtain an inorganic adhesive solution that is not modified by a curing agent;
[0080] ③. Add 5 parts of curing agent and 5 parts of filler to the inorganic adhesive solution that has not been modified by the curing agent, stir for a period of time and then let it stand in air for a period of time to obtain a zinc ion modified aluminum phosphate inorganic adhesive precursor solution;
[0081] ④, transferring the zinc ion modified aluminum phosphate inorganic adhesive precursor solution to a rotary evaporator, removing the water solvent by reduced pressure rotary evaporation, and then drying to obtain a crystalline aluminum dihydrogen phosphate powder modified by a curing agent;
[0082] The mass fraction of concentrated phosphoric acid described in step ① is 70%; the stirring time in step ① is 1 hour, and the stirring speed is 200r / min; the stirring time in step ② is 2 hours, and the stirring speed is 200r / min; the stirring time in step ③ is 2 hours, and the stirring speed is 300r / min; the standing time in step ③ is 15min; the curing agent described in step ③ is zinc oxide powder, and the particle size is 500 mesh to 800 mesh; the particle size of the filler described in step ③ is 80nm to 150nm; the filler described in step (3) is a mixture of silicon powder and aluminum oxide powder, wherein the mass ratio of silicon powder to aluminum oxide powder is 1:1; the drying time of the zinc ion modified aluminum phosphate inorganic adhesive precursor solution in step ④ is 10h.
[0083] Comparative Example 1: The difference between this example and Example 1 is that the mass ratio of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent, the phenolic resin and the organic solvent in the hybrid resin prepreg described in step 2③ is 0:1:1. The other steps and parameters are the same as those in Example 1.
[0084] Example 2: The difference between this example and Example 1 is that the mass ratio of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent, the phenolic resin and the organic solvent in the hybrid resin prepreg described in step 2③ is 1.5:0.5:2. The other steps and parameters are the same as those in Example 1.
[0085] Comparative Example 2: The difference between this example and Example 2 is that the mass ratio of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent, the phenolic resin and the organic solvent in the hybrid resin prepreg described in step 2 ③ is 0:1:1, and the organic solvent described in step 2 ① and step 2 ② is ethylene glycol. The other steps and parameters are the same as those in Example 2.
[0086] Example 3: This example is different from Example 1 in that the mass ratio of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent, the phenolic resin and the organic solvent in the hybrid resin prepreg described in step 2③ is 2.5:0.5:3. The other steps and parameters are the same as those in Example 1.
[0087] Comparative Example 3: The difference between this example and Example 3 is that the organic solvent in step 2① and step 2② is ethylene glycol. The other steps and parameters are the same as those in Example 3.
[0088] Figure 3 This is a comparison chart of the back wall temperature when the surface temperature is stabilized at 1500°C under propane ablation conditions;
[0089] from Figure 3It can be seen that: Example 1, Example 2, Example 3 and Comparative Example 3 all have good thermal insulation performance, and the shielding temperature can reach above 1200°C. The thermal insulation temperature of Example 2 is the highest, reaching 1330.1°C. Since no inorganic precursor is added to Comparative Example 1 and Comparative Example 2, the back temperature is above 400°C, the thermal insulation temperature is less than 1000°C, and all fail to protect the internal structure well. The shielding temperature differences between Example 2, Example 2, Example 3 and Comparative Example 3 are all less than 120°C.
[0090] Figure 4 The photograph and SEM image of a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material prepared in Example 2 after ablation assessment;
[0091] from Figure 4 It can be seen that the silica glass phase on the surface is in a semi-molten state, and is mutually coated and protected with AlPO4, nested layer by layer, while the resin distribution on the fiber bundles of the pyrolysis layer changes from dense to porous, and some fiber bundles lose the protection of the resin matrix and are exposed. These interfaces and pore structures provide space for the flow of pyrolysis gas and the dissipation of heat, and the internal structure is still dense, almost the same as after curing. The material has very excellent thermal insulation properties.
[0092] Figure 5 A comparison chart of the linear ablation rates of a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material prepared in Example 1, Comparative Example 1, Example 2, Comparative Example 2, Example 3, and Comparative Example 3, respectively;
[0093] from Figure 5 It can be seen that the linear ablation rates of Example 1, Example 2, Example 3 and Comparative Example 3 are all less than 0.01 mm / s, and are only 1 / 15 of the linear ablation rate of traditional phenolic resin-based composite materials. As traditional phenolic resin-based composite materials, Comparative Examples 1 and Comparative Examples 2 have extremely high linear ablation rates, and there is a significant ablation recession phenomenon under 1500°C ablation conditions.
[0094] Figure 6 The flexural strength curves of the three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite materials prepared in Example 1, Example 2, and Example 3, respectively.
[0095] from Figure 6 It can be seen that the three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite materials prepared in Example 1, Example 2 and Example 3 respectively have high flexural strength and good engineering service performance, and the maximum flexural strength can reach above 7.12 MPa.
[0096] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material, characterized in that The composite material is aluminum phosphate-phenolic hybrid resin / carbon fiber cloth, wherein the carbon fiber cloth is the skeleton structure of the composite material, and the aluminum phosphate-phenolic hybrid resin is distributed in the carbon fiber skeleton structure in a penetrating attachment manner; the preparation method is specifically completed according to the following steps:
1. Pretreatment of three-dimensional continuous carbon fiber: Removing excess sizing agent and impurities on the surface of the three-dimensional carbon fiber to obtain pretreated carbon fiber; 2. Preparation of hybrid resin prepreg: ①, dissolving phenolic resin in an organic solvent, and stirring thoroughly to obtain a phenolic resin solution; The mass fraction of the phenolic resin solution described in step 2① is 30% to 60%; ②, dissolving the crystalline aluminum dihydrogen phosphate powder modified by the curing agent in an organic solvent, and stirring well to obtain an aluminum dihydrogen phosphate inorganic solution; The mass fraction of the inorganic aluminum dihydrogen phosphate solution described in step 2② is 30% to 60%; ③. Mix the phenolic resin solution and the aluminum dihydrogen phosphate inorganic solution, stir until there is no excess flocculent precipitate in the solution, and let it stand to obtain a hybrid resin prepreg; 3. Preparation of fiber-reinforced hybrid resin: ①, pour the hybrid resin prepreg into a vacuum impregnation container, then press the pretreated carbon fiber into the hybrid resin prepreg, control the internal pressure and temperature of the vacuum drying oven, and then impregnate for a period of time, and then take the wet fiber out of the vacuum impregnation container to obtain a wet fiber precursor; ②, placing the wet fiber precursor in the air and letting it stand for a period of time, and then transferring it to an electric heating blast drying oven for sufficient drying to obtain a fiber-reinforced resin-based composite material prepolymer to be cured; ③. Place the fiber-reinforced resin-based composite material prepolymer to be cured in an electric blast drying oven at room temperature, raise the temperature in the electric blast drying oven from room temperature to the curing temperature, perform gradient cross-linking curing in the range from room temperature to the curing temperature, and exhaust the gas in time. After the curing is completed, take out the obtained composite material and replace the solvent with anhydrous ethanol. Replace the replacement solution at intervals until the solution has no obvious color change, and then dry to obtain a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material.
2. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 1, characterized in that The three-dimensional carbon fiber described in step one has a material with three-dimensional distribution, including a three-dimensional fiber needle-punched structure and a three-dimensional fiber braided structure, and the thickness of the three-dimensional fiber is 8 to 20 mm.
3. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 1, characterized in that The method for removing excess sizing agent and impurities on the surface of the three-dimensional carbon fiber in step one is: placing the three-dimensional carbon fiber in a muffle furnace, heating it to 250°C to 300°C, keeping it warm for 3 to 4 hours, and cooling it to room temperature with the furnace after keeping warm to obtain pretreated carbon fiber; the heating rate is 1°C / min.
4. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 1, characterized in that The organic solvent described in step 2① and step 2② is anhydrous ethanol, isopropanol or ethylene glycol.
5. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 1, characterized in that The preparation method of the crystalline aluminum dihydrogen phosphate powder modified by the curing agent described in step 2② is: (1) Dilute 100 parts of concentrated phosphoric acid with 20 to 80 parts of deionized water and stir for a period of time to obtain a phosphoric acid solution; (2) adding 20 to 50 parts of aluminum hydroxide powder to the phosphoric acid solution, and stirring for a period of time at a temperature of 80° C. to 90° C. to obtain an inorganic adhesive solution that is not modified by a curing agent; (3) adding 2 to 5 parts of a curing agent and 0 to 5 parts of a filler to an inorganic adhesive solution that has not been modified by a curing agent, stirring for a period of time and then air-cooling for a period of time to obtain a zinc ion-modified aluminum phosphate inorganic adhesive precursor solution; (4) The zinc ion-modified aluminum phosphate inorganic adhesive precursor solution is transferred to a rotary evaporator, the water solvent is removed by rotary evaporation under reduced pressure, and then dried to obtain a crystalline aluminum dihydrogen phosphate powder modified by a curing agent.
6. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 5, characterized in that The mass fraction of the concentrated phosphoric acid in step (1) is 50% to 80%; the stirring time in step (1) is 1h to 2h, and the stirring speed is 200r / min to 400r / min; the stirring time at a temperature of 80°C to 90°C in step (2) is 1h to 2h, and the stirring speed is 200r / min to 400r / min; the stirring time in step (3) is 1h to 2h, and the stirring speed is 200r / min to 400r / min; the step (3) is allowed to stand for 1h to 2h, and the stirring speed is 200r / min to 400r / min. The curing time is 10min to 15min; the curing agent described in step (3) is zinc oxide powder with a particle size of 500 mesh to 800 mesh; the particle size of the filler described in step (3) is 80nm to 150nm; the filler described in step (3) is one or a combination of silicon powder, mullite whisker, glass fiber, boron nitride, aluminum oxide, boron carbide and silicon carbide; in step (4), the zinc ion modified aluminum phosphate inorganic adhesive precursor solution is dried for 2h to 10h to ensure that it exists in the form of crystalline powder.
7. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 1, characterized in that The standing time described in step 2③ is 10min to 15min; the mass ratio of the curing agent-modified crystalline aluminum dihydrogen phosphate powder, phenolic resin and organic solvent in the hybrid resin prepreg described in step 2③ is (0.5 to 1.5):(0.5 to 1):(2 to 3).
8. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 1, characterized in that The internal pressure of the vacuum drying oven described in step 3① is less than 0.08MPa, and the temperature is 40℃~60℃; the immersion time described in step 3① is 0.5h~1.5h.
9. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 1, characterized in that In step 3②, the wet fiber precursor is placed in air with a humidity not higher than 40% and allowed to stand for 8h to 10h; after standing in step 3②, it is transferred to an electric heated air drying oven for sufficient drying. The process is: first dry at 90℃ to 100℃ for 0.5h to 1h, and then dry at 120℃ to 150℃ for 2h to 3h.
10. The method for preparing a three-dimensional continuous carbon fiber reinforced organic-inorganic hybrid resin-based composite material according to claim 1, characterized in that The process of gradient cross-linking and curing described in step 3③ is: heating from room temperature to 120℃~150℃, curing at 120℃~150℃ for 2h, then heating to 150℃~180℃, and curing at 150℃~180℃ for 3h; the heating rate is 0.5℃ / min~1℃ / min; after the curing is completed in step 3③, take out the obtained composite material and immerse it in anhydrous ethanol again, replace the anhydrous ethanol every 12h, take it out after changing 3 to 4 times, and then dry it at room temperature for 1 to 2 days.
Citation Information
Patent Citations
Modified carbon fiber reinforced phenolic resin-based composite material and preparation thereof
CN110938281A
Ablation material of phenolic resin impregnated carbon-based three-dimensional woven body and preparation method of ablation material
CN114369269A
High-thermal-conductivity flame-retardant copper-clad laminate and preparation method thereof
CN120461960A
Fiber-resin-carbon composites and method of fabrication
US4215161A